1997
DOI: 10.1097/00005768-199704000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a 1-h endurance performance test in trained female cyclists

Abstract: Endurance performance is a common criterion used to evaluate training or dietary interventions. However, to accurately appraise the effects of an intervention, the endurance performance measure must be reliable. The purpose of the investigation was to establish the reliability of a 1-h endurance performance test. Twenty trained female subjects (peak VO2 = 47.4 +/- 7.2 ml.kg-1.min-1) completed two trials in which they had to generate the highest power output possible throughout 60 min of cycling. Heart rates (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 13 publications
3
20
0
6
Order By: Relevance
“…Our data include the 1999 and 2004 World Cup winners and also, at times, the number one UCI ranked cycling nation in the world, thereby providing an insight into the power demands of some of the best contemporary female cyclists. The calibre of our riders ( _ V O 2peak ¼ 63.8±2.4 mL kg À1 min À1 ) is reinforced by comparable values for the US National Team (63.8±4.2 mL kg À1 min À1 : Wilber et al 1997) and women competing in the Tour of Idaho (64.2±3.9 mL kg À1 min À1 : Pfeiffer et al 1993), but are higher than data reported for an earlier US National Team (57.4±6.6 mL kg À1 min À1 : Burke 1980) and trained female cyclists (47.4±7.2 mL kg À1 min À1 : Bishop 1997). Previous investigations have estimated racing power output based on the HR-power output relationship established in the laboratory ).…”
Section: Discussionmentioning
confidence: 54%
“…Our data include the 1999 and 2004 World Cup winners and also, at times, the number one UCI ranked cycling nation in the world, thereby providing an insight into the power demands of some of the best contemporary female cyclists. The calibre of our riders ( _ V O 2peak ¼ 63.8±2.4 mL kg À1 min À1 ) is reinforced by comparable values for the US National Team (63.8±4.2 mL kg À1 min À1 : Wilber et al 1997) and women competing in the Tour of Idaho (64.2±3.9 mL kg À1 min À1 : Pfeiffer et al 1993), but are higher than data reported for an earlier US National Team (57.4±6.6 mL kg À1 min À1 : Burke 1980) and trained female cyclists (47.4±7.2 mL kg À1 min À1 : Bishop 1997). Previous investigations have estimated racing power output based on the HR-power output relationship established in the laboratory ).…”
Section: Discussionmentioning
confidence: 54%
“…However, these significant changes to substrate metabolism in the luteal phase depend on the ratio of oestrogen to progesterone and the magnitude of the increase in oestrogen from follicular to luteal phase (D'Eon et al 2002), as well as nutritional status . Nonetheless, studies using time to exhaustion at a submaximal intensity are measuring endurance capacity (Bishop 1997) and this favours the metabolic profile associated with the luteal phase as suggested by the findings of some previous studies (Jurkowski et al 1981;Nicklas et al 1989), although not all (Biedleman et al 1999;Bailey et al 2000). Time trials are a better measure of exercise performance (Hickey et al 1992;Jeukendrup et al 1996) and demand greater proportions of carbohydrate oxidation to sustain the high intensity effort.…”
Section: Discussionmentioning
confidence: 99%
“…motivation, monotony and boredom) whereas a time trial has a fixed end point and thus reduces the impact of the psychological factors. Thus, time to exhaustion trials have poor test-retest reliability (coefficient of variation of $27%) (Jeukendrup et al 1996) compared to time trial protocols, which have a greater reproducibility (coefficient of variation of $1-3.4%) (Bishop 1997;Hickey et al 1992;Jeukendrup et al 1996;Palmer et al 1996). Hence, in this study we have chosen to measure performance by means of a cycling time trial.…”
Section: Performance Trialsmentioning
confidence: 99%
“…In broad terms, these tests either measure time to exhaustion at a given workload (Krebs and Powers 1989;Laursen et al 2003b;McLellan et al 1995), measure the time to complete a given amount of work (Hickey et al 1992;Jeukendrup et al 1996), measure the average work done during a given time frame (Bishop 1997;Coyle et al 1991), or the test is a simulated time trial (TT) in which the goal is to cover a given distance in as short a time as possible (Balmer et al 2000;Jensen and Johansen 1998;Palmer et al 1996;Schabort et al 1998;Smith et al 2001;Sporer and McKenzie 2007;Zavorsky et al 2007). Historically, the simulated time trials are accomplished by placing the subject's bicycle onto either an air or magnetically braked stationary trainer, and distance is measured by revolutions of the rear wheel.…”
Section: Introductionmentioning
confidence: 99%